"All shall be happy by land and by sea": Thomas Spence as an Atlantic thinker. Issue 4 (2nd October 2018) - Cazzola, Matilde
ABSTRACT: English radical thinker and activist Thomas Spence (1750–1814) has traditionally been considered a minor figure in the history of political thought. Spence was renowned for his "Plan, " the proposal to abolish the private property of the land and promote a common management of it. His claims for the commons as England underwent industrialization sounded anachronistic at home, but made him relevant from an Atlantic perspective. By insisting on the connection between privatization of land and oppression, Spence linked his agrarian radicalism to the struggles against slavery and the dispossession of the natives in colonial contexts. Experimenting the methodological approach of Atlantic intellectual history from below, this article surveys the Atlantic dimension of Spence's Plan. It discusses Spence's practical and theoretical political education, showing his acquaintance with the landed and maritime struggles of his time and how he translated them into radical political theory. Spence also engaged with modern political thinkers and challenged the modern liberal conceptions of state and empire, assigning a crucial role to the sea as a reservoir of revolutionary ideas and practice. Seen from an Atlantic perspective, Spence's Plan can be interpreted as a project of decolonization of the world. The article traces also Spence's enduring influence, both in England and the Americas. The Atlantic relevance of the Plan is proved by Spence's legacy in the British Caribbean: the connection between land and freedom theorized by Spence was to African slaves a glaring matter of common sense.